The relationship between social safeness and pleasure and resilience levels among university athletes: A descriptive study - Veysel Temel; Nurhan Hümeyra Özçelik (PLoS ONE, 2025)
This study investigates the correlation between social safeness and pleasure and resilience among university students engaged in sports. A total of 350 participants (mean age, 21.09 ± 3.12 years), comprising 239 females and 111 males, were included in the sample. Data collection utilized the "Social Safeness and Pleasure and Resilience Scales". Normality of data was assessed using skewness and kurtosis tests, confirming normal distribution. Pairwise comparisons were conducted using t-tests, multiple comparisons via one-way ANOVA, and relationship analysis employed Pearson Product Moment Correlation. Findings indicate participants scored above mid-level on the social safeness and pleasure scale (Mean = 2.6), and resilience scale (Mean = 3.7). Specifically, social support dimension mean score was above mid-level (Mean = 4.01), emotional coping (Mean = 3.4), and situational coping (Mean = 3.8). Pearson Product Moment Correlation revealed a statistically significant positive relationship between social safeness and pleasure scale scores and resilience scale scores (r = .652, p < .001). This descriptive study sheds light on the interplay between social and emotional factors and resilience among university athletes.